MnNiSi based magnetocaloric alloys for cooling and energy harvesting applications - Kamble, Deepak (Nanyang Technological University, 2019)
Magnetic cooling and energy harvesting technology relies on magnetocaloric materials (MCM). It has several advantages over conventional cooling technology using vapour compression systems. The aim of current research on MCMs are to develop rare-earth free, high performance, low cost, environmentally friendly and readily available materials. Since the last two decades, various MCMs addressing to specific applications have been developed and some of these applications have also been commercialized in recent years. However, most of these materials suffer from various disadvantages such as high cost, low magnetocaloric properties, poor mechanical strength, corrosion, strategic limitations and tedious synthesis routes. Hence, there has been constant endeavors to develop MCMs exhibiting wide tunability of Curie temperature (TC), good performance using low cost raw materials and simple synthesis steps. Such materials are very favorable for cooling and energy harvesting applications. Among the MCMs investigated till date, it is observed that Mn based alloys have the property to exhibit giant magnetocaloric properties. Systematic tuning of the Mn-Mn interatomic spacing can be employed to induce ferromagnetic interactions. MnNiSi alloy was selected as the base material for the present work considering the cost of raw materials. This alloy exhibits both structural transformation and magnetic transition at 1200 K and 600 K, respectively. Substitutional alloying of MnNiSi can decrease the TC and induce a coupling of magnetic and structural transition. Single element substitution by Fe can reduce the TC upto 438 K. To further bring down the TC to near room temperature, double element substitution, e.g., by Fe and Ge, is required. (MnNiSi)1-x(Fe2Ge)x alloys, synthesized by arc melting, exhibited a magnetostructural transition at temperatures ranging from 363 K to 218 K by varying x from 0.32 to 0.36, respectively. The heating and cooling cycles displayed a thermal hysteresis of ~15 K. The steep magnetic transition along with structural transformation resulted in a giant magnetocaloric response with ΔSmax = 57.6 Jkg-1K-1, for a ΔH of 5 T at 301 K for x = 0.34. The alloy with x = 0.35 displayed an RCP of 480 Jkg-1. The phase transition was modeled using Arrott plots, Landau theory and the Bean-Rodbell model to study the first order transition and identify the phase transition parameters. Low cost, Ge-free MnNiSi based alloys, (Mn0.45Fe0.55)Ni(Si1-ySny) were synthesized by arc melting. The TC varied from 352 K to 255 K by varying the Sn content from y = 0.12 to y = 0.18. Magnetostructural coupling was observed for y = 0.12 to 0.16. A decrease in magnetostructural coupling during the first three heating and cooling cycles were observed due to Sn atoms hindering the martensitic phase transition. The magnetocaloric measurements showed reasonable values of ΔSmax = 8.6 Jkg-1K-1 for a field change of 5 T at 315 K for y = 0.14 and the highest RCP of 252 Jkg-1 was displayed by y = 0.18. Cost analysis of the raw materials revealed that the (Mn0.45Fe0.55)Ni(Si1-ySny) are the most inexpensive magnetostructural alloys among MnNiSi alloys. The inexpensive raw materials and good performance makes it a suitable candidate for low cost, near room temperature applications. A thermomagnetic oscillator prototype was fabricated to exploit the thermomagnetic response of (MnNiSi)1-x(Fe2Ge)x alloys. The thermomagnetic alloy (TMA) oscillated between the heat sink and the heat load due to the heating and cooling cycles which changed the magnetic state of the TMA. A hybrid thermomagnetic oscillator was fabricated by coupling the movement of the TMA with another permanent magnet using a spacer. The coupled oscillations generated a voltage output of ~10 V and a cooling of upto 70°C per cycle. The material properties and device parameters were optimized using simulation models and a figure of merit analysis. The material showing the highest figure of merit, i.e., (MnNiSi)0.68(Fe2Ge)0.32 was selected for a given heat load temperature to study the effect of spacer material on the performance. It was revealed that a flexible spacer can increase the oscillation frequency by 32 % and the voltage/cycle by 18% compared to a rigid spacer.